Penganruh Model Pembalajaran Team Based Leraning Terhadap Kemampuan Kolaboratif Peserta Didik Pada Materi Suhu Dan Kalor Di Kelas VII SMP Negeri 3 Satu Atap Taliabu Barat - Amir, Leni Eni (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2025)
This study aims to improve the collaborative skills of seventh-grade students at SMP Negeri 3 Satap Taliabu Barat through the implementation of the Team-Based Learning (TBL) model. The research method used was quantitative, with 36 seventh-grade students at SMP Negeri 3 Satap Taliabu Barat. Data sources came from teachers and students. Data collection techniques used a questionnaire and a collaborative skills test. The data obtained were analyzed descriptively quantitatively. This study was a quasi-experimental study using a nonequivalent control group design and a purposive sampling technique. The sample size was 18 students in the control class and 18 students in the experimental class. The test instrument was an objective essay test with 10 questions, scored from 0 to 1. The results of this study were statistically analyzed using the IBM SPSS version 16 application program, using the "t" test. Based on calculations, the calculated t value was 1.637 and the t table value was 2.064. In accordance with the implementation criteria, the results showed that t-test > t-table at a significance level of 0.05 for the posttest data. Therefore, it can be concluded that the Theme-Based Learning model has an effect and improves students' collaborative skills.